Impact load mitigation in sandwich beams using local resonators. (January 2016) - Sharma, B; Sun, CT
Dynamic response of sandwich beams with resonators embedded in the cores subjected to impact loads is studied. Using finite element models the effectiveness of various local resonator frequencies under a given impact load is compared to the behavior of an equivalent mass beam. It is shown that addition of appropriately chosen local resonators into the sandwich beam is an effective method of improving its flexural bending behavior under impact loads. The effect of a given local resonance frequency under different impact load durations is also studied. It is demonstrated that the choice of appropriate local resonance frequency depends on the impact duration. Further, by performing transverse impact experiments, the finite element models are verified and the advantage of using internal resonators under impact loading conditions is demonstrated.